Kinetika Penyisihan COD dan Pertumbuhan Biomassa pada Aplikasi Lumpur Aktif pada Air Limbah Industri Tahu - Anshah Silmi Afifah; I Wayan Koko Suryawan (Jurnal Ilmu Alam dan Lingkungan, 2020)
Tofu wastewater is one of the residues produced by the industry, where this residue is greater than the product. Activated sludge is one of the conventional wastewater treatment techniques that can be applied to the tofu industry. Kinetic parameters are an important basis in bioreactor design. This study aims to determine the specific growth rate () and the rate of degradation of the substrate (q) in the bioreactor of tofu wastewater treatment with an activated sludge process. This study consisted of three stages, namely acclimatization 1, acclimatization 2, and the process of treating wastewater purely. Specific growth rates at each stage of acclimation 1, acclimation 2, and running were 0.0589 days-1, 0.0539 days-1, and 0.0478 days-1. Whereas the value of substrate removal rate is 0.4591 day-1, 0.4179 day-1, and 0.3761 day-1, respectively.